Godność osoby ludzkiej wymiarem podmiotowości człowieka w gospodarce - Buller, Leszek Jan (Annales. Etyka w Życiu Gospodarczym, 2012)
Poland, after social-politic-economic transformation in 1989, became a capitalistic, free-market country. In this conditions human being can be perceived as an object, not a subject of economic life. Therefore the import ant issue is to take up problems associated with human subjectivity. And human subjectivity is expressed in his personal dignity.